The Value of the Cardiac Magnetic Resonance Intravoxel Incoherent Motion Technique in Evaluating Microcirculatory Dysfunction in Hypertrophic Cardiomyopathy - Alina Abulaiti; Quan Zhang; Haiyan Huang; Shuang Ding; Miriguli Shayiti; Shaoyu Wang; Yunling Wang; Wenxiao Jia (Journal of Interventional Cardiology)
Objective. To evaluate the value of the cardiac magnetic resonance intravoxel incoherent motion (IVIM) technique in microcirculatory dysfunction in patients with hypertrophic cardiomyopathy (HCM). Methods. The medical records of 19 patients with HCM in our hospital from January 2020 to May 2021 were collected retrospectively, and 23 healthy people with a similar age and gender distribution to the patients with HCM were included as controls. All the included subjects underwent clinical assessment and cardiac magnetic resonance imaging. The original IVIM images were analysed, and the imaging parameters of each segment were measured. The HCM group was divided into non-hypertrophic myocardium and hypertrophic myocardium groups. The differences in imaging parameters between the normal and HCM groups were compared. A Spearman correlation analysis was used to explore the correlation between end-diastolic thickness (EDTH) and each IVIM parameter. Results. The D∗ and f values in the HCM group were lower than those in the normal group (p<0.0001 and p=0.004, respectively). The f, D, D∗, and EDTH values of the hypertrophic segment, non-hypertrophic segment, and normal groups were statistically significant (p<0.05). The difference in D∗ values among the mild, moderate, severe, and very severe HCM groups was statistically significant (p<0.05). There was a statistically significant difference in EDTH among the mild, moderate, severe, and very severe groups (p<0.001). There were significant differences in the values of D, D∗, and f between the non-delayed enhancement group and the delayed enhancement group (p<0.05). The EDTH values of 304 segments in the HCM group were negatively correlated with f (r = −0.219, p=0.028) and D∗ values (r = −0.310, p<0.001). Conclusion. The use of IVIM technology can achieve a non-invasive early quantitative assessment of microvascular disease in HCM without the injection of a contrast agent and provide a reference for the early diagnosis of and intervention in myocardial ischemia in patients with HCM.